The bird and the mountains: a note on Psalm 11 - Quine, Cat (Brill, 2017)
This paper demonstrates that the bird and the mountains phrase in Ps 11:1 compares well with a common metaphor relating to siege warfare and military conquest found in Neo-Assyrian royal inscriptions and considers the resulting implications.